2017
DOI: 10.1177/2333392817721648
|View full text |Cite
|
Sign up to set email alerts
|

Six-Month Outcomes for Collaborative Care Management of Depression Among Smoking and Nonsmoking Patients

Abstract: Background:Collaborative care management (CCM) is an evidence-based model that contributes to better outcomes for depression treatment in the primary care setting. Tobacco use increases overall economic costs, morbidity, and mortality and has been shown to impact behavioral health outcomes. Our study aims to observe clinical outcomes for depression treatment for patients with comorbid tobacco use and depression within the CCM model.Methods:A retrospective chart review study of 2826 adult patients with depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 74 publications
1
3
1
Order By: Relevance
“…As expected based on prior work, multivariate analysis of remission revealed that most DOC-6 components (age, recurrent depression, initial PHQ-9 score, GAD-7 score, and MDQ), smoking status, and enrollment in CCM were all significantly associated with adjusted remission odds as shown in Fig. 3 [14, 17, 27, 29, 30]. Rural patients had improved adjusted odds of remission (AOR = 2.8, 95%CI 1.4–5.9) compared to urban area patients while urban cluster patients were not different.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…As expected based on prior work, multivariate analysis of remission revealed that most DOC-6 components (age, recurrent depression, initial PHQ-9 score, GAD-7 score, and MDQ), smoking status, and enrollment in CCM were all significantly associated with adjusted remission odds as shown in Fig. 3 [14, 17, 27, 29, 30]. Rural patients had improved adjusted odds of remission (AOR = 2.8, 95%CI 1.4–5.9) compared to urban area patients while urban cluster patients were not different.…”
Section: Resultssupporting
confidence: 66%
“…Distance from the patient’s address to their primary care clinic was calculated in kilometers using the Haversine formula [26]. The other independent variables were included to adjust depression outcomes as they are known to be significant [17, 27].…”
Section: Methodsmentioning
confidence: 99%
“…44 Similar to our previously published results within CCM, smoking was associated with worse depression outcomes than nonsmokers. 41 Contrary to our hypothesis, we did not observe a difference in depression outcomes between smokers and nonsmokers treated with UC. With less collaborative care and lack of consistent psychotherapy resources, UC has lower odds of remission than CCM irrespective of smoking status.…”
Section: Discussioncontrasting
confidence: 99%
“…44 Similar to our previously published results within CCM, smoking was associated with worse depression outcomes than nonsmokers. 41…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation